Particle beam dynamics in a magnetically insulated coaxial diode - Korenev, V.G.; Magda, I.I.; Sinitsin, V.G. (Вопросы атомной науки и техники, 2015)
The dynamics of charged particle beams emitted from a cathode into a smooth coaxial diode with magnetic insulation is studied with the aid of 3-D PIC simulation. The processes controlling space charge formation and its evolution in the diode are modeled for geometries typical of high-voltage millimeter wave magnetrons that are characterized by very high values of emission currents, hence high space charge densities.